Uberlândia: os condomínios verticais fechados e a produção do espaço urbano - Medeiros, Carlos de Sousa; Soares, Beatriz Ribeiro (Sociedade & Natureza, 2021)
Uberlândia: os condomínios verticais fechados e a produção do espaço urbano